2004
DOI: 10.1111/j.0887-378x.2004.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating a Public Health Approach in Drug Law: Lessons from Local Expansion of Treatment Capacity and Access under California's Proposition 36

Abstract: A major state drug abuse initiative, California's Proposition 36 of 2000, mandated that adults convicted of drug possession be offered treatment in lieu of incarceration. While the law expanded public treatment for arrestees, the counties were given discretion in structuring their systems of care and procedures to manage clients. Using data from a study of key informants in eight counties, this article examines local planning to increase drug treatment capacity and manage clients' access to treatment. In both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Early concerns expressed about Proposition 36 related to the effectiveness of treatment and the quality of treatment provided (Riley et al, 2000;Young & Belenko, 2002). Another concern was that Proposition 36 clients would be less engaged in treatment because they were there by external mandate rather than by internal motivation, and so they would have shorter stays in treatment and poorer outcomes (Klein et al, 2004;Speiglman et al, 2003). This study found no evidence that treatment outcomes were different between the two groups.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Early concerns expressed about Proposition 36 related to the effectiveness of treatment and the quality of treatment provided (Riley et al, 2000;Young & Belenko, 2002). Another concern was that Proposition 36 clients would be less engaged in treatment because they were there by external mandate rather than by internal motivation, and so they would have shorter stays in treatment and poorer outcomes (Klein et al, 2004;Speiglman et al, 2003). This study found no evidence that treatment outcomes were different between the two groups.…”
Section: Discussionmentioning
confidence: 73%
“…One of the earlier concerns with Proposition 36 was the client's lack of engagement in treatment participation (Klein et al, 2004;Speiglman et al, 2003). Using data collected in the course of a larger treatment outcome study (Andrews, Sorensen, Guydish, Delucchi, & Greenberg, 2005), this paper reports substance abuse, criminal justice and employment outcomes, and retention in treatment for a sample of residential therapeutic community (TC) participants referred through California's Proposition 36.…”
Section: Introductionmentioning
confidence: 99%
“…Jurisdictional, or county-level, variation has been reported in SACPA program operations [8,[18][19][20][21][22][23][24][25], characteristics of participating offenders [18], and outcomes [26].…”
Section: Contextual Variationmentioning
confidence: 99%
“…Probationers or parolees who violate drug-related conditions of community supervision are also eligible. In operation since 2001, SACPA implementation successfully applied a public health approach to drug-related offending, reducing drug use among offenders [7,8]. Many drug-abusing offenders entered treatment within a very short time period [9], and the program resulted in favorable outcomes, especially among treatment completers [10], while yielding noteworthy cost savings [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation